Dietary Plant Lectins Appear to Be Transported from the Gut to Gain Access to and Alter Dopaminergic Neurons of Caenorhabditis elegans, a Potential Etiology of Parkinson’s Disease - Zheng, Jolene; Wang, Mingming; Wei, Wenqian; Keller, Jeffrey N.; Adhikari, Binita; King, Jason F.; King, Michael L.; Peng, Nan; Laine, Roger A. (Frontiers in Nutrition, 2016)
Lectins from dietary plants have been shown to enhance drug absorption in the gastrointestinal tract of rats, be transported trans-synaptically as shown by tracing of axonal and dendritic paths, and enhance gene delivery. Other carbohydrate-binding protein toxins are known to traverse the gut intact in dogs. Post-feeding rhodamine- or TRITC-tagged dietary lectins, the lectins were tracked from gut to dopaminergic neurons (DAergic-N) in transgenic Caenorhabditis elegans (C. elegans) (egIs1[Pdat-1::GFP]) where the mutant has the Green Fluorescent Protein (GFP) gene fused to a dopamine transport protein gene labeling dopaminergic neurons, The lectins were supplemented along with the food organism Escherichia coli (OP50). Among nine tested rhodamine/TRITC-tagged lectins, four, including Phaseolus vulgaris erythroagglutinin (PHA-E), Bandeiraea simplicifolia (BS-I), Dolichos biflorus agglutinin (DBA), and Arachis hypogaea (PNA), appeared to be transported from gut to the GFP-DAergic-N. Griffonia Simplicifolia (GSL-I) and PHA-E, reduced the number of GFP-DAergic-N suggesting a toxic activity. PHA-E, BS-I, Pisum Sativum (PSA), and Triticum vulgaris agglutinin (Succinylated) reduced fluorescent intensity of GFP-DAergic-N. PHA-E, PSA, Concanavalin A, and Triticum vulgaris agglutinin decreased the size of GFP-DAergic-N, while BS-I increased neuron size. These observations suggest that dietary plant lectins are transported to and affect DAergic-N in C. elegans, which support Braak and Hawkes’ hypothesis, suggesting one alternate potential dietary etiology of Parkinson’s disease (PD). A recent Danish study showed that vagotomy resulted in 40% lower incidence of PD over 20 years. Differences in inherited sugar structures of gut and neuronal cell surfaces may make some individuals more susceptible in this conceptual disease etiology model.